Counseling and education on adequacy of vitamin and mineral intake from fruit and vegetables to improve body immunity in senior high school students in Tanjung Morawa district - Sinaga, Siti Morin; Silalahi, Jansen; Cintya, Henni (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2020)
Fruits and vegetables are food ingredients that contain a lots of nutrients such as vitamins, minerals and fiber that are needed by the body. Indonesia is a country that is very rich in fruits and vegetables. However, in fact, fruits and vegetables are rarely consumed by people, especially teenagers. Lack of intake in consuming fruits and vegetables can cause the body to lack nutrients such as vitamins, minerals, fiber and an imbalance in the body's acid and alkaline, which can lead to various diseases. The purpose of this community service is to provide counseling and educate students and teachers about the adequate intake of vitamins and minerals from fruits and vegetables to increase immunity in Senior High School students in Tanjung Morawa District. This community service activity was carried out by means of a lecture method by disseminating the activity plan to the children of the Yayasan Pendidikan Pauly Mandiri students, then demonstrations by conducting counseling. Community service activities in general received a very good response and high enthusiasm from students, and several teachers who attended and the chairman of the Pauly Mandiri Education Foundation in Tanjung Morawa asked to be resumed. The results of community service, especially practicing how to create fruits and vegetables by making salads from various fruits and vegetables that can be applied by students and teachers in their daily lives. The enthusiasm of the participants hoped that this outreach activity could be resumed, namely how to make it easier for children to make it easier for children to remember the importance of consuming fruits and vegetables.